2013
DOI: 10.1124/dmd.112.050609
|View full text |Cite
|
Sign up to set email alerts
|

The Inactivation of Human CYP2E1 by Phenethyl Isothiocyanate, a Naturally Occurring Chemopreventive Agent, and Its Oxidative Bioactivation

Abstract: Phenethylisothiocyanate (PEITC), a naturally occurring isothiocyanate and potent cancer chemopreventive agent, works by multiple mechanisms, including the inhibition of cytochrome P450 (P450) enzymes, such as CYP2E1, that are involved in the bioactivation of carcinogens. PEITC has been reported to be a mechanismbased inactivator of some P450s. We describe here the possible mechanism for the inactivation of human CYP2E1 by PEITC, as well as the putative intermediate that might be involved in the bioactivation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…These antioxidants, contained in many fruits and vegetables, show beneficial effects on AFLD, NAFLD, and DILI, although some of these antioxidants also exhibit significant protection in other tissues such as heart, muscle, and brain (Pallauf, Giller, Huebbe, & Rimbach, 2013;Rodriguez et al, 2015). Some of these agents include inhibitors of CYP2E1 such as diallyl sulfide in garlic, phenethyl isothiocyanate (Stice et al, 2015;Yoshigae, Sridar, Kent, & Hollenberg, 2013) in crucible vegetables, or dioscin in edible plants , although these inhibitors seem less potent than the synthetic CYP2E1 inhibitor CMZ (Hu et al, 1994) or YH439 ( Jeong et al, 1996). In addition, general antioxidants such as SAMe and betaine were shown to preserve mitochondrial function and proteome in the animal models of AFLD Purohit et al, 2007) and NAFLD (Santamaria et al, 2003), partly through blocking the ROS/RNS production and restoring the physiological levels of GSH, SAMe, and S-adenosyl-homocysteine.…”
Section: Translational Research Opportunitiesmentioning
confidence: 99%
“…These antioxidants, contained in many fruits and vegetables, show beneficial effects on AFLD, NAFLD, and DILI, although some of these antioxidants also exhibit significant protection in other tissues such as heart, muscle, and brain (Pallauf, Giller, Huebbe, & Rimbach, 2013;Rodriguez et al, 2015). Some of these agents include inhibitors of CYP2E1 such as diallyl sulfide in garlic, phenethyl isothiocyanate (Stice et al, 2015;Yoshigae, Sridar, Kent, & Hollenberg, 2013) in crucible vegetables, or dioscin in edible plants , although these inhibitors seem less potent than the synthetic CYP2E1 inhibitor CMZ (Hu et al, 1994) or YH439 ( Jeong et al, 1996). In addition, general antioxidants such as SAMe and betaine were shown to preserve mitochondrial function and proteome in the animal models of AFLD Purohit et al, 2007) and NAFLD (Santamaria et al, 2003), partly through blocking the ROS/RNS production and restoring the physiological levels of GSH, SAMe, and S-adenosyl-homocysteine.…”
Section: Translational Research Opportunitiesmentioning
confidence: 99%
“…Indeed, PEITC is a potent mechanism-based inhibitor of cytochrome P450 enzymes Modulation of carcinogen metabolism by PEITC 7 both in rat and human microsomes, far more effective than the aliphatic isothiocyanates sulforaphane and erucin (Konsue & Ioannides, 2010a,b;Yoshigae et al, 2013). Using recombinant human cytochrome P450 enzymes, it was established that PEITC was a mechanism-based inhibitor of CYP2E1 (Nakajima et al, 2001).…”
Section: Modulation Of Cytochrome P450 Activity and Expression By Peitcmentioning
confidence: 99%
“…Using recombinant human cytochrome P450 enzymes, it was established that PEITC was a mechanism-based inhibitor of CYP2E1 (Nakajima et al, 2001). In the same system, it was demonstrated that PEITC acted as a mechanism-based inhibitor by interacting with both the heme and protein moieties of cytochrome P450, with the latter being the principal inactivation route (Yoshigae et al, 2013). Phenethyl isocyanate, generated by the cytochrome P450-catalyzed oxidative desulfuration of PEITC was initially considered the likely metabolite responsible for the inhibitory effect (Lee, 1996) but this was shown not to be the case in subsequent studies (Konsue & Ioannides, 2010b).…”
Section: Modulation Of Cytochrome P450 Activity and Expression By Peitcmentioning
confidence: 99%
“…Inhibition of Phase I metabolizing enzymes is one of the prominent mechanisms of chemoprevention by ITCs (Fig. 3) [112][113][114][115]. Morse et al and several other studies have mechanistically shown that ITCs prevent tumorigenesis caused by various chemical carcinogens in vivo [115][116][117].…”
Section: Biochemical Mechanisms Of the Chemopreventive Effects Of Itcsmentioning
confidence: 99%
“…3) [112][113][114][115]. Morse et al and several other studies have mechanistically shown that ITCs prevent tumorigenesis caused by various chemical carcinogens in vivo [115][116][117]. PEITC exhibits marked chemopreventive effect against tobacco-induced lung and esophageal cancer in rodent models [118,119].…”
Section: Biochemical Mechanisms Of the Chemopreventive Effects Of Itcsmentioning
confidence: 99%